Theoretically improved biodegradability of fluoroquinolones in sewage and sludge - Yajing Liu; Xingyan Jin; Rui Fu; Yu Li; Wenwen Wang (Ecotoxicology and Environmental Safety)
Fluoroquinolones (FQs), recognized for their potent antibacterial activity, have been extensively used in clinical and veterinary medicine. However, their low removal efficiency during sewage treatment and the emergence of drug resistance have raised significant concerns. In this study, a molecular “design-screening-validation-mechanism analysis” approach was developed to design FQ alternatives with improved removal efficiency and reduced drug resistance. Among 180 designed alternatives, eight were selected based on high removal efficiency in sewage and sludge and low drug resistance, using three-dimensional structure-activity relationship analysis, molecular docking, and molecular dynamics simulations. Subsequently, their pharmacological functionality, human health risks, and ecological impacts were evaluated through pharmacokinetic and toxicokinetic models and ADMETlab, narrowing the candidates to one compound (CIP-129–28-40). Further analyses of CIP-129–28-40 included sludge adsorption, biodegradability, and drug resistance mechanisms. Results indicated that hydrogen bonding and dipole moment significantly contributed to enhanced sludge adsorption and biodegradability. Additionally, ordered changes in the secondary structure of proteins during binding were identified as the primary factor influencing drug resistance. This study provides theoretical support for designing environmentally friendly FQ alternatives with enhanced removal efficiency and reduced bacterial resistance, advancing the understanding of their ecological risks.